ANALYSIS OF THE SOUNDSCAPE OF SKI RESORTS IN BAD HOFGASTEIN (AUSTRIA) AND BIAŁKA TATRZAŃSKA (POLAND) - Magdalena Maria Malec; Tomasz Kotowski (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: Firstly, due to the different sizes and spatial organization of ski resorts, it is important to determine whether there is a local differentiation of the sound landscape within one resort. Secondly, due to the continuous expansion of the ski infrastructure, it is essential to develop methods for improving the quality of the acoustic environment. It is therefore necessary to determine whether there are acoustic differences between the different ski resorts.